Pengaruh Quality Of Work Life (Qwl), Komunikasi Dan Organizational Citizenship Behavior (Ocb) Terhadap Kinerja Karyawan Pada PDAM Kota Malang - Ita Kurniawati; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractGood performance in terms of quality and quantity enables the vision, mission and goals of the organization to be achieved. The purpose of this study was to examine the influence of Quality of Work Life, Communication and Organizational Citizenship Behavior on Performance at PDAM Malang City. This type of research uses a quantitative approach. From the results of this study, the following results were obtained: (1) simultaneously, the variables of Quality of Work Life, Communication and Organizational Citizenship Behavior had a significant positive effect on performance. (2) partially, the variable Quality of Work Life has a significant positive effect on performance. (3) the communication variable has a significant positive effect on performance. (4) Organizational Citizenship Behavior variable has a significant positive effect on performance. This means that the higher the level of Quality of Work Life, Communication and Organizational Citizenship Behavior, the higher the performance. And vice versa, the lower the level of Quality of Work Life, Communication and Organizational Citizenship Behavior, the lower the performance. Keyword : Quality of Work Life, Communication, Organizational Citizenship Behavior and  Performance